Price Regulation in Telecommunications Sector and Its Implications (The Pakistan Development Review, 1999)
Telecommunication facility has been provided in most countries as a user pay public service managed, typically, through the Post, Telegraph and Telephone departments or by some government-owned monopoly. The tradition has been to regard it as a natural monopoly to be supplied by the public sector.1 This perception has changed. Telecommunication is now increasingly recognised as a prime mover of the modern day economy. It is opening to participation by the private sector. The economic benefits of telecommunications are enormous, both as a growth industry in its own right and in terms of its impact on economic development. It has a significant social role in transforming how people communicate, become informed or do business. Additionally, it is also environment-friendly because it disseminates information without shifting goods or people. The practice now in vogue is to establish a regulatory agency with a high degree of independence from both operator and government. The regulator’s task is to implement government policy, ensure performance accountability by the operators and other players in respect of economic and social policy objectives, resolve disputes between competitors, monitor changing industry conditions and advise government on developments bearing on policy. The regulatory agency acts as a buffer between telecom operators and government, helping to ensure the separation of functions.